The Impact of Neem Leaf Extract (Azadirachta indica) on renal hypoxia in Balb/C Mice Infected with Plasmodium berghei - Rahmah, Zainabur; Religious, Tafakur Bagus; Akbar, Putri Wulan; Kosbandhono, Erryk; Amiruddin, Muhammad; Nashichuddin, Ach (Faculty of Medicine, UIN Syarif Hidayatullah Jakarta, 2025)
Background: Millions of people die from malaria every year in tropical areas, making it a severe public health concern. Plasmodium, a genus of protozoa with several species, is the main cause of the disease. Humans contract malaria when bitten by female Anopheles sp. mosquitoes. Malaria is one of the world's deadliest diseases. The WHO's 2020 World Malaria Report indicates that there were 229 million cases of malaria globally in 2019, with 409,000 fatalities resulting from the disease. In nine Southeast Asian countries, malaria is endemic. After India, Indonesia is the second most endemic region. Transcription factors such as the HIF-1α protein are produced by hypoxic cells. Patients with malaria have a blockage of the cytoaderenal pathway. Hypoxia occurs due to vascular disorders that prevent oxygen flow to the kidney tissue. Antimalarial drugs are developed in response to the lethal consequences of hypoxia. Methods: BALB/c mice aged sixteen weeks were infected with the Plasmodium berghei ANKA strain. For six days, the neem leaf 96% ethanol extract was administered orally at doses of 8 mg, 12 mg, and 16 mg. As comparisons, negative, positive, and healthy controls were also included. The kidneys were isolated, and the mice were surgically removed on the seventh day. HIF-2α expression in kidney tissue, which was measured immunohistochemically using Abcam's anti-HIF-2α (H1α67) ChIP Grade antibody, was a characteristic of kidney hypoxia. One-way ANOVA, post-hoc LSD, and Pearson correlation tests were used to assess the hypotheses. Results: Treatment with neem leaf extract significantly decreased oxygen levels (p<0.000). The correlation test showed a very strong relationship between neem leaf extract and HIF-2α expression in the kidney (r=16.057). Conclusion: Twelve milligrams of neem leaf extract can reduce the risk of renal hypoxia. Keywords: Neem leaves, malaria, degree of parasitemia, hypoxia, Azadirachta indica